Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the system of equations:
[tex]\[ y = x + 3 \][/tex]
[tex]\[ y = x^2 - 2x - 1 \][/tex]
we need to find the points (x, y) that satisfy both equations simultaneously. Here are the detailed steps:
1. Set the Equations Equal to Each Other:
Since both expressions are equal to \( y \), we can set them equal to each other to find the values of \( x \):
[tex]\[ x + 3 = x^2 - 2x - 1 \][/tex]
2. Rewrite the Equation:
Rearrange the equation to set it to zero:
[tex]\[ x^2 - 2x - x - 1 - 3 = 0 \][/tex]
This simplifies to:
[tex]\[ x^2 - 3x - 4 = 0 \][/tex]
3. Solve the Quadratic Equation:
To solve the quadratic equation \( x^2 - 3x - 4 = 0 \), we can either factorize or use the quadratic formula. This particular quadratic can be factored:
[tex]\[ (x - 4)(x + 1) = 0 \][/tex]
Setting each factor to zero gives us the solutions:
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
[tex]\[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \][/tex]
4. Find Corresponding \( y \)-Values:
Now we need to find the corresponding \( y \)-values for each \( x \):
- For \( x = 4 \):
[tex]\[ y = 4 + 3 = 7 \][/tex]
So, one solution is \( (4, 7) \).
- For \( x = -1 \):
[tex]\[ y = -1 + 3 = 2 \][/tex]
So, another solution is \( (-1, 2) \).
5. List the Solutions:
The solutions to the system are the points where the lines intersect. These points are:
[tex]\[ (-1, 2) \][/tex]
[tex]\[ (4, 7) \][/tex]
6. Compare with Options:
Given the options:
- A: \((1, 4)\) and \((-4, -1)\)
- B: \((-1, 4)\) and \((4, -1)\)
- C: \((-1, 7)\) and \((4, 2)\)
- D: \((-1, 2)\) and \((4, 7)\)
We see that option D: \((-1, 2)\) and \((4, 7)\) matches our solutions perfectly.
Thus, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
[tex]\[ y = x + 3 \][/tex]
[tex]\[ y = x^2 - 2x - 1 \][/tex]
we need to find the points (x, y) that satisfy both equations simultaneously. Here are the detailed steps:
1. Set the Equations Equal to Each Other:
Since both expressions are equal to \( y \), we can set them equal to each other to find the values of \( x \):
[tex]\[ x + 3 = x^2 - 2x - 1 \][/tex]
2. Rewrite the Equation:
Rearrange the equation to set it to zero:
[tex]\[ x^2 - 2x - x - 1 - 3 = 0 \][/tex]
This simplifies to:
[tex]\[ x^2 - 3x - 4 = 0 \][/tex]
3. Solve the Quadratic Equation:
To solve the quadratic equation \( x^2 - 3x - 4 = 0 \), we can either factorize or use the quadratic formula. This particular quadratic can be factored:
[tex]\[ (x - 4)(x + 1) = 0 \][/tex]
Setting each factor to zero gives us the solutions:
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
[tex]\[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \][/tex]
4. Find Corresponding \( y \)-Values:
Now we need to find the corresponding \( y \)-values for each \( x \):
- For \( x = 4 \):
[tex]\[ y = 4 + 3 = 7 \][/tex]
So, one solution is \( (4, 7) \).
- For \( x = -1 \):
[tex]\[ y = -1 + 3 = 2 \][/tex]
So, another solution is \( (-1, 2) \).
5. List the Solutions:
The solutions to the system are the points where the lines intersect. These points are:
[tex]\[ (-1, 2) \][/tex]
[tex]\[ (4, 7) \][/tex]
6. Compare with Options:
Given the options:
- A: \((1, 4)\) and \((-4, -1)\)
- B: \((-1, 4)\) and \((4, -1)\)
- C: \((-1, 7)\) and \((4, 2)\)
- D: \((-1, 2)\) and \((4, 7)\)
We see that option D: \((-1, 2)\) and \((4, 7)\) matches our solutions perfectly.
Thus, the correct answer is:
[tex]\[ \boxed{D} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.